The association between rapid antiretroviral therapy initiation and brain structure and function based on multimodal magnetic resonance imaging in HIV-positive men who have sex with men - Yihui He; Yang Zhang; Taiyi Jiang; Miaotian Cai; Guangqiang Sun; Yundong Ma; Jiahao Ji; Bo Yang; Bin Yang; Junyi Duan; Dongxia Wu; Lijun Sun; et al. (BMC Infectious Diseases)
Abstract An increasing number of treatment guidelines recommend rapid initiation of antiretroviral therapy (ART) after the diagnosis of human immunodeficiency virus (HIV) infection. However, data on the association between rapid ART initiation and alterations in brain structure and function remain limited in people with HIV (PWH). A cross-sectional analysis was conducted on HIV-positive men who have sex with men (MSM) undergoing ART. Fifty-four participants who started ART within 30 days of confirmed HIV diagnosis (rapid ART group) and 20 participants who started ART more than 6 months of confirmed HIV diagnosis (non-rapid ART group) completed clinical assessments and multimodal magnetic resonance imaging scans to obtain both anatomical and resting-state functional images. Compared to PWH in the non-rapid ART group, those in the rapid ART group exhibited a greater total gray matter volume (P = 0.001) and functional changes, including a lower amplitude of low-frequency fluctuations in the left angular gyrus (P < 0.001). Moreover, the results of the main effects and interactions indicated that rapid ART initiation had main effects on major imaging outcomes. The validation analysis results in participants who started ART within 7 days of confirmed HIV diagnosis generally corroborated and complemented the aforementioned findings. Our study demonstrated brain gray matter volume atrophy and functional alterations in PWH of the non-rapid ART group compared to those in the rapid ART group, suggesting that rapid ART initiation may be associated with better brain structure and function changes in HIV-positive MSM.